Evaluation of the Character Home Visit Program Using the Context, Input, Process, Product (CIPP) Model at SMP Islam Al Madinah Jombang - Aristanti, Suci; Bachri, Bachtiar Sjaiful; Maureen, Irena Yolanita (CV. Pusdikra Mitra Jaya, 2024)
Evaluation of the character program at SMP Islam Al Madinah Jombang is very important to determine the effectiveness of the program in developing moral and ethical values ??among students. This evaluation can also help identify deficiencies and errors in the character program, so that better improvements and development can be made. This research aims to find out how to evaluate the character home visit program. Research using the CIPP evaluation model includes Context, Input, Process, Product. Data collection techniques use interview, observation and documentation methods.The data analysis used is data collection, data reduction, data presentation, and verification or drawing conclusions. The results of the program evaluation include (1) in terms of context, the components are home visit background, character, social conditions of students, and school policies. (2) in terms of input, the components are available resources, teacher preparation, and parental involvement. (3) viewed from the process, its components are planning, implementation, evaluation and challenges. (4) in terms of product, the components are the impact of student behavior, parental satisfaction with program results, and recommendations for program improvement and development.